Strategi Memulai Usaha Di Masa Pandemi Covid 19 - Sarah Robiatul Adawiyah; Neng Asri Sri Lestari (Jurnal Pendidikan Islam dan Manajemen Ekonomi, 2023)
The COVID-19 pandemic that hit the world, especially in Indonesia, caused almost all economic sectors to be paralyzed. Many businesses are not running, some are even forced to close. However, in this new normal era, not a few intend to start a new business. Activities to build a business in the midst of a pandemic must be carried out with careful planning. Because basically, one of the keys to successfully starting a business is the ability to put creative, innovative, and high economic value ideas or ideas into a mature and realistic business plan supported by good strategy implementation. Some steps that can be taken to start a business during a pandemic are checking financial conditions, compiling a business plan, analyzing market needs, determining the right target market, paying attention to supplier problems, and providing the best service to customers.